Acceptability to general practitioners of national health insurance and capitation as a reimbursement mechanism - Blecher, Mark Stephen (Department of Public Health and Family Medicine, 2017)
Objective: The objectives of the study were to determine General Practitioners' attitudes to National Health Insurance (NHI) and to capitation as a mechanism of reimbursement. The study also aimed to explore determinants of these attitudes. Design: The methodology utilised a cross-sectional survey using telephone interviews and four focus group discussions. Setting: The study area was the Cape Peninsula area in the Western Cape Province of South Africa. Participants: 174 general practitioners (GPs) were randomly sampled from a total population of 874 GPs in the Cape Peninsula area. Main outcome measures: The main outcome measures were GPs' acceptance of NHI and of capitation as a method of reimbursement. Main results: Sixty three percent of GPs (63,3%) approved of NHI. More than 81 % approved of NHI if GPs were to maintain their independent status, for example their own premises and working hours. Eighty two percent (82,3%) said NHI would be a more equitable system of health care than the system that existed at that time, 88% approved of the fact that NHI would make care by GPs more accessible and 73% said they had the capacity to treat more patients. However, 61,3% of GPs disapproved of capitation as a form of reimbursement. The most common conditions cited by GPs for support of NHI were retention of professional autonomy, fee for service reimbursement and adequate levels of reimbursement. Conclusions: Most GPs in the Cape Peninsula were amenable to some form of NHI. However, approval of NHI is to some extent conditional to details of the NHI system, such as payment mechanisms, workload, income and effects on professional autonomy. The implications of GPs' preferences concerning the reimbursement mechanism for the feasibility of implementing a NHI in South Africa requires serious consideration by policy makers. While this research demonstrates broad ideological and conceptual support for some form of NHI or SHI, further research is required to provide more detailed quantitative information on the trade-offs that GPs would be prepared to make for them to support the introduction of a new socially based insurance system. A national survey of medical practitioners is recommended.